The demand for organic food in Kota Kinabalu, Sabah - Fadzedah Noor Gulamhaidar; Janice L. H. Nga; Jonghyun Park (GRRI, 2019)
This study aimed to examine the determinants affecting the demand for organic food in Kota Kinabalu. The variables are adapted and extended from the studies of Uesangkomsate and Santiteerakul (2016: 426), Husniyah Abd Rahim (2015: 542) and Kulikovski and Agolli (2010: 51-52) namely health consciousness, concern over food safety, ethical concern, perception of quality, trust in labeling and marketing and price premium. The combination of all three models has derived a model with six factors based on a traditional theory of demand. Responses from 326 respondents obtained from a survey conducted on a paper-based as well as on electronic-based. The multiple regression was used to test the hypothesis postulated. It is discovered that only two out of six variables are significant which is the level of health awareness among consumers and price premium between organic and non-organic food. By having a better understanding of the demand of organic food in Kota Kinabalu, the policy maker i.e. government and marketers can make better strategies to entice the consumer to purchase organic food. Additionally, suppliers can act accordingly to reach the rising demand and finally, theoretical contribution of this study is an extension of literature to the body of knowledge.